Invariance of Measures of Prevention Program Effectiveness: A Replication - Rosay, André B. (Journal of quantitative criminology, 2000)
Recent literature has suggested that measures of risk and protective factorsfor delinquency and substance use are not equally reliable or valid acrossgender and ethnic groups and has recommended differentiated programming andculturally specific evaluation methods. Three data sets containing up tofive ethnic groups were used to determine the degree to which risk andprotective factors are equally reliable and valid predictors of drug use anddelinquency across gender and ethnic groups. Congeneric measurement modelsand structural equation models were evaluated to determine if the factorstructures for these measures and their covariances with measures of druguse and delinquency were equivalent across gender and ethnic groups. Half ofthe risk and protective factors included in this analysis were found to beequally reliable across gender and ethnic groups. When controlling forreliability differences, all of the risk and protective factors were foundto predict both drug use and delinquncy for all gender and ethnic groups. Interms of the magnitude of these associations, no substantive differenceswere found in the validity of risk and protective factors for drug use anddelinquency. Differences in the validity of risk and protective factors weremore prevalent for delinquency than for drug use. However, all differenceswere substantively trivial. We conclude that measures of prevention programeffectiveness are invariant across gender and ethnic groups.